A Case of a 4-Year-Old Boy with a Mesenteric Chylous Cyst Infected with Histoplasma capsulatum. (6th January 2016) - Kweyamba, Vianney; Apiyo, Mirraim; Olika, Biratu; Kituuka, Olivia
Abstract : Mesenteric cysts are uncommon entities and chyle- (lymph-) containing cysts are the rarest of this group. This is a case report of a 4-year-old boy with a mesenteric chylous cyst who was later found to have Histoplasma capsulatum infection.